Cricket singing means rain: semiotic meaning of insects in the district of Pedra Branca, Bahia State, northeastern Brazil - Costa Neto,Eraldo M. (2006)
This paper deals with the semiotic meanings which are given both to the appearance and/or behavior of insect species according to the ethnoentomological knowledge of the inhabitants of the village of Pedra Branca, Bahia State, Brazil. Data were collected from February to May 2001 by performing open-ended, recorded interviews with nine men and twenty-five women, whose ages ranged from 19 to 82 years old. Data were analyzed by using the union model, which involves considering all available information on the surveyed subject. Twelve kinds of insects were associated with both beneficial and harmful events, as well as with the indication of changing weather. The way local people perceive and interpret the appearance and/or behavior of certain species of insects depends on the cultural background of each inhabitant. The following semiotic meanings were recorded: fatal, funereal, auspicial, meteorological, societal, monetary, and of abundance or scarcity. The beliefs in the augural power of insects in the village of Pedra Branca are deep-rooted in the local tradition and are transmitted from generation to generation through oral culture. It is hoped that the data now available will be incorporated into a curriculum by those researchers interested in insect conservation and ethnobiology as well.